Trinidad and Tobago : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Trinidad and Tobago. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses economic developments, outlook, and risks in Trinidad and Tobago. The economic output of Trinidad and Tobago has continued to shrink. Ongoing maintenance and further declines in gas and oil production are estimated to have driven energy output 4.7 percent lower (year over year) as of September 2015. The longstanding current account surplus turned into a 5.4 percent of GDP deficit in 2015. The significant terms-of-trade shock implies that the real effective exchange rate has become more overvalued. Risks to growth are tilted to the downside, and much will depend on the authorities' ability to navigate the transition to the lower energy price environment.